2018
DOI: 10.1101/344606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardioprotection by the mitochondrial unfolded protein response (UPRmt) is mediated by activating transcription factor 5 (ATF5)

Abstract: The mitochondrial unfolded protein response (UPR mt ) 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Liquid-cultured cells are provided with moderate culture density, sufficient nutrients, and a suitable environment, whereas tumor cells face monoclonal expansion pressures in semisolid cultures and experience nutrient deficiency and hypoxia in xenograft models. Accumulating evidence suggests that ATF5 acts as a prosurvival factor under cellular stress (31)(32)(33). To assess the involvement of ATF5 in the stress response in CTCL, we exposed the liquid-cultured CTCL cell lines Myla and H9 to various stress-inducing conditions and assessed their impact on ATF5 expression.…”
Section: Atf5 Protects Malignant T Cells Against Endoplasmic Reticulu...mentioning
confidence: 99%
“…Liquid-cultured cells are provided with moderate culture density, sufficient nutrients, and a suitable environment, whereas tumor cells face monoclonal expansion pressures in semisolid cultures and experience nutrient deficiency and hypoxia in xenograft models. Accumulating evidence suggests that ATF5 acts as a prosurvival factor under cellular stress (31)(32)(33). To assess the involvement of ATF5 in the stress response in CTCL, we exposed the liquid-cultured CTCL cell lines Myla and H9 to various stress-inducing conditions and assessed their impact on ATF5 expression.…”
Section: Atf5 Protects Malignant T Cells Against Endoplasmic Reticulu...mentioning
confidence: 99%
“…ATF5 has been proposed to drive the protective effect of UPRmt in different diseases models such as osteoarthritis (Zhou et al, 2022), heart failure (Smyrnias et al, 2019;Wang et al, 2019), and protect host during enteric infection (Chamseddine et al, 2022). In our experimental system, we show that ATF5 is essential for the upregulation of the UPRmt markers in cells subjected to mitochondrial stress but is not involved in SG dynamics.…”
Section: Cells Unable To Assemblementioning
confidence: 99%
“…Key to maintaining or adapting mitochondrial functions, the mitochondrial unfolded protein response (UPRmt) is an evolutionarily conserved mitochondria-tonucleus signalling cascade, initially described as a transcriptional response to the accumulation of misfolded mitochondrial proteins (Martinus et al, 1996;Zhao et al, 2002). Studies have shown that activation of the UPRmt is primarily regulated by the Activating Transcription Factor 5 (ATF5) (Fiorese et al, 2016;Smyrnias et al, 2019;Wang et al, 2019), and engaged upon a wide range of mitochondrial insults, including abnormal level of mitochondrial reactive oxygen species (ROS) (Wang et al, 2022b), dissipation of mitochondrial membrane potential (Rolland et al, 2019), and reduced mitochondrial protein import efficiency (Nargund et al, 2012). Activated UPRmt serves to restore mitochondrial protein homeostasis and promote cell survival in various biological processes, such as innate immune signalling (Pellegrino et al, 2014) and ageing (Houtkooper et al, 2013), as well as adaptation to pathophysiological conditions, such as neurodegenerative disorders (Sorrentino et al, 2017) and cardiovascular diseases (Smyrnias et al, 2019;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 377 upregulated genes and 84 downregulated genes were detected at 2 dpi, and 259 upregulated genes as well as 52 downregulated genes at 5 dpi (Figure 4A, Figure S4B, and Table S2-S3). The top-10 upregulated genes on both days include genes associated with protection of cardiac tissue damage and mitochondria metabolism (Apod, Atf5, Mthfd2) (Tsukamoto et al, 2013;Wang et al, 2019), IFN-I response (Ifi27, Ddx60, Serping1), cytokine signaling : black and open dots). Mock-infected mice were measured to establish the background level.…”
Section: Chikv-infected Cardiac Tissue Induces Ifn-i Signaling In Bot...mentioning
confidence: 99%